The Present And Future Design of The Modernization Fund and Its Implementation Across EU and In Romania - Daniela ZĂNESCU (PANAIT) (Communications of International Proceedings, 2022)
This paper completes the empirical literature on the EU ETS from the point of view of the policy design and implementation of low carbon technologies and the modernization of the energy infrastructure. In this respect, it is analysed the use of the Modernization Fund under the phase IV of ETS in year 2021, across EU and in Romania. At the same time, the paper depicts its future architecture from the legislative proposals under the Fit for 55 package. The current research goes further the overview that I previously presented in 2019 on the arhitecture of EU Emission Trading System and its specific funding mechanisms up to 2030 considering that Teixido, Verde, Nicolli, 2019 supports the idea that the EU ETS reform for Phase IV enhanced financial support for low carbon investments through dedicated funds, namely the Modernization Fund and the Innovation Fund.
Keywords: Emissions trading; EU ETS design and evaluation; Modernisation Fund; Low carbon techologies